Vernal keratoconjunctivitis: A severe allergic eye disease with remodeling changes. Issue 4 (20th January 2014) - Vichyanond, Pakit; Pacharn, Punchama; Pleyer, Uwe; Leonardi, Andrea
Abstract Vernal keratoconjunctivitis (VKC) is an unusually severe sight‐threatening allergic eye disease, occurring mainly in children. Conventional therapy for allergic conjunctivitis is generally not adequate for VKC. Pediatricians and allergists are often not familiar with the severe clinical symptoms and signs of VKC. As untreated VKC can lead to permanent visual loss, pediatric allergists should be aware of the management and therapeutic options for this disease to allow patients to enter clinical remission with the least side effects and sequelae. Children with VKC present with severe ocular symptoms, that is, severe eye itching and irritation, constant tearing, red eye, eye discharge, and photophobia. On examination, giant papillae are frequently observed on the upper tarsal conjunctiva (cobblestoning appearance), with some developing gelatinous infiltrations around the limbus surrounding the cornea (Horner‐Trantas dot). Conjunctival injections are mostly severe with thick mucus ropy discharge. Eosinophils are the predominant cells found in the tears and eye discharge. Common therapies include topical antihistamines and dual‐acting agents, such as lodoxamide and olopatadine. These are infrequently sufficient and topical corticosteroids are often required for the treatment of flare ups. Ocular surface remodeling leads to severe suffering and complications, such as corneal ulcers/scars. Other complications include side effects from chronic topical steroids use, such as increased intraocular pressure, glaucoma, cataract and infections. Alternative therapies for VKC include immunomodulators, such as cyclosporine A and tacrolimus. Surgery is reserved for those with complications and should be handled by ophthalmologists with special expertise. Newer research on the pathogenesis of VKC is reviewed in this article. Vernal keratoconjunctivitis is a very important allergic eye disease in children. Complications and remodeling changes are unique and can lead to blindness. Understanding of pathogenesis of VKC may lead to better therapy for these unfortunate patients.